Detection Detection Of Methicillin Resistant Staphylococcus aureus (MRSA) On The Patients Of RSUD Dr. Moewardi surakarta Using Culture Method And Polymerase Chain Reaction (PCR) - Siti Nur Arsih; Nony Puspawati; Rizal Maarif Rukmana (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
ABSTRACT Methicillin Resistant Staphylococcus aureus (MRSA) is type of Staphylococcus aureus resistant to beta-lactam antibiotics, such as meticillin, penicillin, amphycillin, and amoxycillin. The percentage of MRSA occurrence in Indonesia is quite high namely 23.5%. MRSA detection can be done using culture method and Polymerase Chain Reaction (PCR). This research aims to find out the comparison of speed and sensitivity between the culture method and Polymerase Chain Reaction (PCR) in detecting Methicillin Resistant Staphylococcus aureus towards the patients of RSUD Dr. Moewardi Surakarta. This research used experimental analytic research design along with comparative research design. This experiment observed 3 samples of bacterial isolates Staphylococcus aureus MRSA suspect patients of RSUD Dr. Moewardi Surakarta. The detection of MRSA was conducted using disk diffusion test of penicillin, amphycillin, amoxycillin and vancomisin as well as using Polymerase Chain Reaction (PCR). The results of the research indicate that Polymerase Chain Reaction (PCR) method was faster and more sensitive to detect Methicillin Resistant Staphylococcus aureus on the patients of RSUD Dr. Moewardi Surakarta.